Dabigatran ameliorates post-haemorrhagic hydrocephalus development after germinal matrix haemorrhage in neonatal rat pups. Issue 9 (September 2017) - Klebe, Damon; Flores, Jerry J; McBride, Devin W; Krafft, Paul R; Rolland, William B; Lekic, Tim; Zhang, John H
We aim to determine if direct thrombin inhibition by dabigatran will improve long-term brain morphological and neurofunctional outcomes and if potential therapeutic effects are dependent upon reduced PAR-1 stimulation and consequent mTOR activation. Germinal matrix haemorrhage was induced by stereotaxically injecting 0.3 U type VII-S collagenase into the germinal matrix of P7 rat pups. Animals were divided into five groups: sham, vehicle (5% DMSO), dabigatran intraperitoneal, dabigatran intraperitoneal + TFLLR-NH2 (PAR-1 agonist) intranasal, SCH79797 (PAR-1 antagonist) intraperitoneal, and dabigatran intranasal. Neurofunctional outcomes were determined by Morris water maze, rotarod, and foot fault evaluations at three weeks. Brain morphological outcomes were determined by histological Nissl staining at four weeks. Expression levels of p-mTOR/p-p70s6k at three days and vitronectin/fibronectin at 28 days were quantified. Intranasal and intraperitoneal dabigatran promoted long-term neurofunctional recovery, improved brain morphological outcomes, and reduced intracranial pressure at four weeks after GMH. PAR-1 stimulation tended to reverse dabigatran's effects on post-haemorrhagic hydrocephalus development. Dabigatran also reduced expression of short-term p-mTOR and long-term extracellular matrix proteins, which tended to be reversed by PAR-1 agonist co-administration. PAR-1 inhibition alone, however, did not achieve the same therapeutic effects as dabigatran administration.